1999
DOI: 10.1111/j.1528-1157.1999.tb01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonepileptic Seizures After Resective Epilepsy Surgery

Abstract: Summary:Purpose: To identify factors that are associated with the emergence of nonepileptic seizures (NES) after resective epilepsy surgery.Methods: Twenty-two patients with medically refractory epilepsy in whom NESs were documented by EEG after resective surgery were compared with a larger series of epilepsy surgery patients on demographic, neurologic, and psychiatric variables.Results: NES tended to become apparent in the first few months after surgery. Patients who developed NESs did not differ from other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 24 publications
(11 reference statements)
7
45
4
Order By: Relevance
“…They suggested that a low full-scale IQ, preoperative psychiatric comorbidity, and major surgical complications could be potential risk factors. In a study of 220 patients, 22 (10 %) developed postsurgical de novo PNES [ 35 ]. In this study, preoperative psychopathology was not identifi ed, in contrast to the other studies and our own data (see above) [ 11 ].…”
Section: Psychogenic Non-epileptic Seizurescontrasting
confidence: 78%
“…They suggested that a low full-scale IQ, preoperative psychiatric comorbidity, and major surgical complications could be potential risk factors. In a study of 220 patients, 22 (10 %) developed postsurgical de novo PNES [ 35 ]. In this study, preoperative psychopathology was not identifi ed, in contrast to the other studies and our own data (see above) [ 11 ].…”
Section: Psychogenic Non-epileptic Seizurescontrasting
confidence: 78%
“…Previous studies have identified potential risk factors for the development of NES after cranial surgery to treat intractable epilepsy (6,8,9). We compared the patients in the present study with patients in a larger group representative of our surgical population, and found that there were no significant differences with respect to ages at the time of surgery and epilepsy onset, duration of epilepsy, FSIQ, proportion of each sex, side of surgery, seizure outcome, and proportion with IDD preoperatively.…”
Section: Risk Factors For Development Of De Novo Nesmentioning
confidence: 73%
“…Glosser et al included in their series of 9 patients whose NES morphology consisted solely of minor symptoms: 6 patients experienced panic, 1 anxiety, 1 somnolence, and 1 visual hallucinations (6). These symptoms indeed may occur as simple partial seizure events but their inclusion as NES can be questioned.…”
Section: Incidence Of Postoperative De Novo Nesmentioning
confidence: 97%
See 1 more Smart Citation
“…Some anesthetic agents can also trigger seizures [4]. Glosser et al [5] reported nonepileptic seizures after cranial surgery to treat intractable epilepsy. Despite these previous reports, nonepileptic seizures are rare complication after general anesthesia and are classified as either physiologic or psychogenic in origin.…”
Section: Discussionmentioning
confidence: 98%